Dental trauma associated with high impact sport - Goiato, Marcelo Coelho [UNESP]; Da Rocha Bonatto, Liliane [UNESP]; Da Silva, Emily Vivianne Freitas [UNESP]; Vechiato-Filho, Aljomar José [UNESP]; De Medeiros, Rodrigo Antônio [UNESP]; Dos Santos, Daniela Micheline [UNESP] (Wolters Kluwer, 2015)
The objective of this study was to report a case of tooth fracture during the sport practice and the treatment performed for the patient. A 17-year-old male patient was subjected to an endontic treatment followed by the reattachment of the fractured teeth. Teeth were endodontically treated by conventional method. After, the acid etching with 37% phosphoric acid gel was performed and a bonding agent was applied on the dental surface. The fragments were reattachment and bonded with minimum amount of composite resin since the teeth/fragment interface was small. The occlusal contacts were adjusted in the finish line of restorations with a diamond bur and the polishing was performed with aluminum oxide discs. Positive esthetical and periodontal outcomes with no complications in the endodontic treatment were observed on radiographic examinations after twelve months of follow up. The endodontic treatment associated with the reattachment of the fractured teeth by a bonding procedure was a conservative treatment for the patient. The use of mouthguards is important to prevent such dramatic events.
Keywords: Athletic Injuries; Dental Bonding; Injuries; Sports Medicine